The role of the Judiciary Power in its fight against corruption: external and internal order - Távara Córdova, Francisco (2007)
The Judicial Power constitutes the main called institution within a Constitutional State, to fight against the corruption. This certainly, within a frame of cooperation with other institutions. Since the beginning of the year 2001, the legislation and actions destined to revert the judicial corruption have been increased, emphasizing the role of the judicature throughout new schemes of performance like the sub system of anticorruption, whose competition has been extended, and also the continuous and recognized work of the Office of Control of Judges (Oficina de Control de la Magistratura -OCMA). The judicial reform been applied in our country points out that the fight against the corruption happens to fortify the existing institutions, in order to consolidate a system of justice equipped with impartial, independent, effective and efficient organs in Peru. To accomplish that purpose is necessary to put in practice a set of actions as well as the promotion of some values and a public ethic in our society, which, accompanied by a greater transparency, constitute an authentic policy of prevention of the corruption.